Key pathways and genes in hepatitis B virus-related liver inflammation: Expression profiling and bioinformatics analysis. Issue 34 (26th August 2022) - Zhao, Jing-Yuan; Zhong, Zhao-Zhong; Zhao, Li-Yun; Li, Wen
Abstract : Chronic hepatitis B virus infection has become a major public health issue worldwide, which can lead to liver inflammation, fibrosis, and hepatocellular carcinoma. According to the inflammation activity, liver tissues can be divided into 5 grades (G0–G4). However, the mechanism of the development of liver inflammation remains unclear. In our study, expression profiling by microarray and bioinformatics technology was used to systemically identify differentially expressed genes (DEGs) between low grades (G0–G1) and high (G2–G4) grades of liver inflammation. Gene Ontology (GO) enrichment analysis, Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis, and protein–protein interaction network construction were performed for further identification of the key functions, pathways, and hub genes that might play important roles in the inflammation development. A total of 1982 DEGs were identified, consisting of 1220 downregulated genes and 762 upregulated genes. GO analysis revealed the DEGs were mainly enriched in GO terms that related to neutrophil activation and degranulation. MAPK1, ITGA2, CDK2, TGFB1, CDKN2A, MTOR, IL6, PCNA, OAS2, and EP300 were hub genes that had the highest centricity and might be potential markers for inflammation development. This study identified the differentially expressed genes between different grades of inflammation, which would enlighten the study that focuses on the mechanism of liver inflammation development.